Intra-hospital cardiorespiratory arrest in COVID-19 patients: Integrative review (Research, Society and Development, 2022)
The objective of this research was to establish the agreement between the presence of coronavirus 2019 infection and the episode of in-hospital cardiac arrest and the importance of care for patients hospitalized for COVID-19. This is an integrative literature review study, where the search for studies was carried out in the NCBI/PubMed (National Center for Biotechnology Information), SciELO (Scientific Electronic Lirary Online), Google Scholar and Regional Portal databases. from the VHL (Virtual Health Library Regional Portal). In order to delimit the contents, inclusion criteria were used: studies related to infection, cardiorespiratory arrest and myocardial injury in patients with COVID-19, considering those published in the year 2019 to the year 2022. The exclusion criteria were: texts incomplete, studies that did not assess the repercussions of cardiac arrest, or studies that assessed other outcomes. There was no restriction on language and type of study. From the analysis of the articles, it was noticed that, although COVID-19 is an infection, mainly of a respiratory nature, it also has negative impacts on the cardiovascular system (CVS), with cardiac arrest being common in hospital settings. and one of the main causes of death from this disease, being a challenge to health professionals. It was concluded that critically ill patients with COVID-19 are at high risk of developing in-hospital cardiac arrest and there are few chances of positive outcomes, demonstrating the importance of health professionals being prepared to care for these patients.